Criminal Law Review of Meth Sales Transactions Which are Evidenced by Police Officers According to Law Number 35 of 2009 Concerning Narcotics in the Jurisdiction of the Bukit Tinggi Police - Kusno Kusno; Ahmad Ansyari Siregar; Risdalina Risdalina; Bernat Panjaitan; Sopian Sopian (Journal of Social Research, 2023)
Article 44 of Law Number 8 of 1981 concerning the Criminal Procedure Law regulates the governance of evidence. This study aims to find out and analyze criminal law arrangements for police members who abuse narcotics and psychotropics. As well as knowing and analyzing the policies of the chief of police of the Republic of Indonesia regarding law enforcement against members of the Indonesian national police who are involved in criminal acts of drug abuse. This research belongs to the normative type of research. So that it can be known that the legal process against the police who commit criminal acts is in accordance with Article 29 paragraph (1) of Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia. Police officers must carry out a police code of conduct hearing, and if proven guilty by being sentenced to more than 5 (five) years. Then the police officer can be immediately dismissed with disrespect from his agency or removed from office if the sentence imposed is less than 5 (five) years. In addition, the increasing number of Narcotics cases among Police officials is a result of the weak implementation of the law among the police.